Pengaruh Ukuran Perusahaan,Umur Perusahaan,Komite Audit, Profitabilitas, dan Solvabilitas Terhadap Audit Delay pada Perusahaan Manufaktur pada Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia - Arie Pratania Putri; Anugrah Gabe Simanjuntak; Afridesi Manalu (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study was conducted to determine the relationship between firm size, firm age, audit committee, profitability, and solvency on audit delay, in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2016-2019 period. The data used in this journal is sourced from the annual report data of companies listed on the Indonesia Stock Exchange through the official website www.idx.co.id. The method used in this research is the comparative casual method. The research population was 12 companies, with 4 years of total observations, so the number of research samples was 48. Documentation technique is a technique used in this study using multiple linear regression and data processed through SPSS version 22 program. Based on partial testing that the variable size companies and audit committees have a positive effect on audit delay. While the variable age of the company, profitability and solvency variables have no effect on audit delay.